UPAYA GURU DALAM MENGATASI KEBINGUNGAN SISWA MENGGUNAKAN METODE CERAMAH PLUS TANYA JAWAB DALAM PEMBELAJARAN DARING - Olang, Jemry Bernabas; Soesanto, Robert Harry (DIDAKTIKA, 2022)
The COVID-19 pandemic requires teachers to conduct online learning. Monotonous online learning using the lecture method causes a lack of interaction between teachers and students, causing confusion. Thus we need a method that can facilitate the teacher to explain the material by involving students in learning. Thus, researchers use the lecture method plus question and answer as one way to overcome student confusion in online learning. In conducting research, researchers use descriptive qualitative methods that emphasize literature review. Giving the lecture method plus question and answer to overcome student confusion is a form of teacher responsibility to God. Through the provision of this method the teacher can show his dedication to God by being responsible for overcoming students' confusion. The lecture plus question and answer method can overcome student confusion by providing space for students to ask questions or express their confusion in both synchronous and asynchronous learning. Researchers suggest teachers to continue to encourage students not to feel ashamed and afraid to be considered stupid when students express their confusion. The teacher must also give appreciation in the form of applause, words of praise, and so on as a form of motivation to students so that they can express their confusion.Keywords: confusion, responsibility, lecture method plus question and answer